Impacts of a Changing Ecosystem on the Feeding and Feeding Conditions for Atlantic Salmon During the First Months at Sea - Utne, Kjell Rong; Skagseth, Øystein; Wennevik, Vidar; Broms, Cecilie Thorsen; Melle, Webjørn; Thorstad, Eva B. (Frontiers in Marine Science, 2022)
During the last decades, many wild Atlantic salmon populations have declined dramatically. One hypothesis for an observed reduction in salmon marine growth and survival is reduced abundance of prey. However, the effect of spatial and temporal variation in marine prey abundance on post-smolt feeding conditions is poorly understood. Here we use stomach content data from 2572 salmon post-smolts sampled during 25 years in the Northeast Atlantic Ocean to examine spatial and temporal changes in diet and stomach fullness. Sandeel larvae west of Scotland and Ireland and in the northern North Sea, herring larvae in the eastern part of the Norwegian Sea, and amphipods in the western part of the Norwegian Sea were particularly important prey species. There was a reduction of fish larvae in the post-smolt stomachs over a large geographic area when comparing the period 1995–2004 to 2008–2019. This may be result of a bottom-up driven process, as increasing extent of Arctic Water masses and zooplankton abundance were positively correlated with post-smolt stomach fullness in the Norwegian Sea. Furthermore, the interspecific competition for fish larvae between post-smolts and mackerel may have increased with a larger mackerel stock expanding the feeding migrations northwards since 2007.